ESTUDIO CLÍNICO-RADIOGRÁFICO COMPARATIVO DEL RECUBRIMIENTO PULPAR INDIRECTO CON PASTA A BASE DE UNCARIA TOMENTOSA VS. HIDRÓXIDO DE CALCIO Y CEMENTO ÓXIDO DE ZINC - EUGENOL. - Lahoud S., Víctor (2000)
90 premolares and molares diagnosed with deep caries groud with symptoms of reversable pulpitis, were divided in 3 groups: Group I, 30 teeth having indirect pulp cap (IPC) Uncaria tomentosa; Group II, 30 teeth having indirect pulp cap with calcium Hidroxyde; Group III, 30 teeth having on indirect pulp cap with Zinc Oxide Eugenol. The clinical radiographic study 90 days demostrated comparativity the advantages of the aplication of Uncaria Tomentosa in the Indirect pulp Cap over the utilization of Calcium Hidroxyde and Zinc Oxide-Eugenol. The treatment using Uncaria tomentosa demostrated the elimitation of pulpar inflamation and pain, mantaining of vitality of the pulp, negative percussion, normal periodontal ligament, abscence of periapical reactivity, and the formation of reparative dentin in 90% of the cases, this is comparasion to calcium hidroyxide wihich should the same results in only 83,3 % of the cases, and 73,3 % of the cases using Zinc Oxide - Eugenol.